DETOXIFICATION OF TRYPSIN INHIBITORS IN THE KERNEL CAKE OF JATROPHA CURCAS BY REGULATING ITS INHIBITORY ACTIVITY AND ITS EFFECT ON COMMON CARP FISHES: Life Sciences-Bio Chemistry - MARTIN MANOAH.I; DR. NAZEEMA.T.H (International Journal of Life Science and Pharma Research, 2022)
Biodiesel has attracted its considerable attention during the past decade as a renewable, biodegradable and non-toxic fuel source for alternative to fossil fuels. Biodiesel can be obtained from vegetable oils (both edible and non-edible) and also from animal fat. Jatropha curcas Linnaeus, a multipurpose plant, which contains high amount of oil in its seeds which can be converted to biodiesel. J. curcas is probably the most highly promoted oil seed producing crop at present in the world. The presence of oil in the seeds helps in the process of biodiesel production. After the oil extraction process, the kernel cakes were dumped as a waste product called bio- mass. The kernel cake generated as a by-product of oil production was rich in protein, which can be used as potential stock for animal feed. But the problem is the presence of toxic substances like Phorbol esters and trypsin inhibitors. The main objectives of the study are to detoxification of these toxins and to reuse the waste product as a live stock feed. SDSpage helps in isolating the bands of the trypsin inhibitors. Researchers universally have studied that these trypsin inhibitors and investigated ways of improving and detoxifying the kernels and applications of the seed meal on live stock. This review paper outlines the previous research done on the Jatropha curcas plant, the toxicity due to Trypsin inhibitors and the efforts made to detoxifying the seed. It also stated that these treated kernels can be used as a live stock feed. Here common carp fish was used in the toxicological studies which are closely related to the human as food. It also highlights the knowledge gaps concerning the chemistry of trypsin inhibitors toxicity and the probable areas for the future research.